Problems related to gynaecological and obstetric care in Poland-selected issues - Katarzyna Plagens-Rotman; Piotr Merks; Michalina Drejza; Magdalena Pisarska-Krawczyk; Witold Kędzia; Grażyna Jarząbek-Bielecka (IMR Press, 2021)
Introduction: Obstetric and gynaecological care are undoubtedly one of the most important elements in protecting a woman's health. From the period of puberty characterised by many hormonal changes, until late old age, every woman should be cared for depending on her age and state of health. However, women and girls living in rural areas have difficulties in accessing reproductive health care, especially public services that are financed by the National Health Fund (Narodowy Fundusz Zdrowia - NFZ). There is a significant gap in access to antenatal and gynaecological health care services between women living in urban and rural areas. Objective: The goal of this paper is to explore current state of knowledge and data from recent reports on access to reproductive health care services in rural areas of Poland with a special focus on people living with disabilities and to share recommendations and solutions to improve access to universal reproductive healthcare services. Conclusions: Family policy should be coordinated with health policy to ensure comprehensive, tailored and free maternal and child healthcare at primary, local and national levels. The observed insufficient access to obstetric and gynaecological care in rural areas is probably associated with increased outlays, and thus the more efficient functioning of health care facilities in large cities. Additional campaigns, introducing mobile clinics and quality improvement in fulfilling the national standards of antenatal and gynaecological care are pivotal to universal access of reproductive health services of Polish women. People living with disabilities are facing structural and information barriers in order to access reproductive health services they need and deserve. Efforts should be made in order to develop the standards of care in order to facilitate and increase access to obstetrics and gynaecological care.